Methodology for prioritizing marine environmental pressures under various management scenarios in the Black Sea - Lazar, Luminita; Spanu, Alina; Boicenco, Laura; Oros, Andra; Damir, Nicoleta; Bisinicu, Elena; Abaza, Valeria; Filimon, Adrian; Harcota, George; Marin, Oana; Pantea, Elena; Timofte, Florin; et al. (Frontiers in Marine Science, 2024)
This study aims to develop a methodology for identifying predominant pressures on the marine ecosystem, emphasizing the significance of examining these pressures and the necessity for management scenarios. The research focuses on how the Black Sea ecosystem responds to the combined effects of human pressures, climate change, and policies. An in-depth analysis was conducted on environmental pressures affecting the Romanian Black Sea, highlighting dominant pressures such as physical habitat loss, hydrocarbon introduction, and non-indigenous species invasion. The research employs a novel methodological approach to assess the implications of these pressures under different Shared Socioeconomic Pathways (SSPs): SSP1 “Taking the Green Road”, SSP2 “Middle of the Road”, and SSP5 “Taking the Highway”. The findings reveal a complex interplay between economic development and environmental conservation, with each pathway presenting distinct outcomes for marine ecosystems. Recent developments, including beach rehabilitation, maritime transport, and oil and gas exploitation, have overshadowed traditional pressures such as nutrient introduction and fishing. The study identifies the increasing vulnerability of critical habitats to anthropogenic pressures, with the rehabilitation of these ecosystems remaining challenging even under reduced pressures. The results underscore the need for adaptive management strategies to enhance the Black Sea ecosystem’s sustainability and resilience. The study’s insights are important for developing management strategies that address ongoing environmental challenges. This research provides knowledge for policymakers and stakeholders involved in marine management and conservation efforts in the Black Sea region, emphasizing the importance of adaptive strategies to mitigate the adverse effects of human activities and climate change on marine ecosystems.